A critical review of nutrition resources for general practitioners focusing on a healthy diet, including seafood - Taylor, Jane; McManus, Alexandra; Nicholson, Claire (Australasian Medical Journal Pty Ltd, 2011)
Background: General practitioners (GPs) are considered a trusted and reliable source of health-related information including nutritional advice. Preliminary investigation found that GPs wanted evidence-based nutrition resources that could be used within a 10 minute consultation. Aim: The aim of the study was to identify and critically review current resources available to GPs that promote seafood consumption within a healthy diet, as a preventative or treatment measure for common lifestyle or medical conditions. Methods: English language resources currently available to GPs in 2008 were sourced through multiple avenues including: individual organisations; medical service networks; health information services and internet search engines. Assessment included critical review of: format; appropriateness for target groups; reference to seafood and supporting evidence; credibility; readability; and suitability for use by practitioners in a short consultation. Results: One hundred and twenty resources were identified. The majority (88.4%, n=106) of identified resource were available electronically. Just over half (57.5%, n=69) of the resources were targeted at specific audiences. All of the resources made reference to the health benefits of regular consumption of fish (100%, n=120), 22.5% (n=27) made reference to seafood in general and 5% (n=6) made reference to fish oil. Only 15% (n=18) of the identified resources were suitable for use with the general Australian population at or below the recommended reading level of Year Eight. The majority (87.5%, n=105) of the identified resources were associated with credible sources of information about the health benefits of regular consumption of seafood.Conclusions: This study found that the majority of resources available to GPs were not suitable for use with the general Australian population at the recommended reading level of Year 8 or lower. Whilst it is acknowledged that written health information alone cannot change health behaviours, it can provide accurate information to assist in making changes to behaviours with support from appropriate health care professionals.